Investigation on the effects of halo implants for nanoscale vertical MOSFET - Ismail, Razali (2007)
To provide a platform for discussions of Solid State Science and Technology in all aspects of physical properties, chemistry, characterizations, preparation methods, optical properties, macro-,micro- and nano-structures. Besides that, modeling, simulation, measurement techniques as well as current development in technology will also be discussed.